2020
DOI: 10.1101/2020.07.16.207894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intracellular Group AStreptococcusinduces Golgi fragmentation to impair host defenses through Streptolysin O and NAD-glycohydrolase

Abstract: Group A Streptococcus (GAS; Streptococcus pyogenes) is a major human pathogen that causes streptococcal pharyngitis, skin and soft-tissue infections, and life-threatening conditions such as streptococcal toxic-shock syndrome. During infection, GAS not only invades diverse host cells, but also injects effector proteins such as NAD-glycohydrolase (Nga) into the host cells through a streptolysin O (SLO)-dependent mechanism without invading the cells; Nga and SLO are two major virulence factors that are associated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Thus, GAS EVs also contribute to modulation of host inflammatory responses in various ways. Our previous work demonstrated that the inflammatory response is attenuated by disruption of the Golgi complex and the post-Golgi secretory pathway during the GAS invasion process ( Nozawa et al., 2021 ). Hence, the results of the present study imply that attenuation of the inflammatory response is triggered by living bacterial cells and bacterial component-containing EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GAS EVs also contribute to modulation of host inflammatory responses in various ways. Our previous work demonstrated that the inflammatory response is attenuated by disruption of the Golgi complex and the post-Golgi secretory pathway during the GAS invasion process ( Nozawa et al., 2021 ). Hence, the results of the present study imply that attenuation of the inflammatory response is triggered by living bacterial cells and bacterial component-containing EVs.…”
Section: Discussionmentioning
confidence: 99%